Plants Are Not Boring, School Botany Is - Nataša Kletečki; Dario Hruševar; Božena Mitić; Andrej Šorgo (MDPI AG, 2023)
The quality of botanical education depends on the quality and interests of the teacher. The aim of our paper was to conduct an initial study on the attitudes of primary and secondary school teachers about plants and botany. We initiated a study in which 211 biology and 168 teachers of different subjects, from primary to secondary schools in Croatia, participated on a voluntary basis. Statistical analysis was processed using jamovi 2.3 software. Teachers of all profiles (biology and others) had similar attitudes: high opinion about the importance of plants for life and education but not about school botany; botany was in the middle of their scale for potential exclusion from education. The last part of the survey referred only to biology teachers and their interests and suggestions for increasing the attractiveness of botany as a subject. The results showed that botany was the least popular, and within it, teachers were most interested in ecology and horticulture. They suggested that botany would be more interesting with active teaching methods and references to everyday contexts; however, it remains unclear why that is so, as the level of autonomy they are given does enable them to introduce such changes.